2022
DOI: 10.3390/cells11071132
|View full text |Cite
|
Sign up to set email alerts
|

Baicalein Activates Parkin-Dependent Mitophagy through NDP52 and OPTN

Abstract: The elimination of intracellular components by autophagy maintains metabolic homeostasis and is a quality-control pathway that enables organelle regeneration. Mitophagy is a type of selective autophagy that regulates mitochondrial turnover, and the dysregulation of mitophagy has been implicated in the pathogenesis of liver diseases. However, the detailed molecular mechanism underlying mitophagy regulation in liver cells remains unclear, and the small molecules that may potentially modulate hepatic mitophagy ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 90 publications
(148 reference statements)
0
4
0
Order By: Relevance
“…NIX, a protein on the outer membrane of mitochondria, recruits LC3 II/I to form autophagosomes that wrap damaged mitochondria. This autophagy process can help to maintain intracellular stability by allowing damaged mitochondria to be cleared [ 43 , 44 ]. Thus, mitochondrial function is thought to be closely related to DDP resistance.…”
Section: Discussionmentioning
confidence: 99%
“…NIX, a protein on the outer membrane of mitochondria, recruits LC3 II/I to form autophagosomes that wrap damaged mitochondria. This autophagy process can help to maintain intracellular stability by allowing damaged mitochondria to be cleared [ 43 , 44 ]. Thus, mitochondrial function is thought to be closely related to DDP resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Activated Parkin recruits OPTN proteins into the mitochondria. With the increasing number of OPTN proteins, mitochondrial autophagy is activated ( Ke et al, 2022 ). Some researchers have found that in AD, Aβ exposure can induce the activation of PINK1/Parkin/OPTN pathway, upregulate the expression level of OPTN, and initiate mitochondrial autophagy to reduce the accumulation of Aβ.…”
Section: Discussionmentioning
confidence: 99%
“…NIX, a protein on the outer membrane of mitochondria, recruits LC3 II/I to form autophagosomes that wrap damaged mitochondria. This autophagy process can help to maintain intracellular stability by allowing damaged mitochondria to be cleared [43,44]. Thus, mitochondria function is thought to be closely related to DDP resistance.…”
Section: Discussionmentioning
confidence: 99%